Advanced research of social networks’ communication: An analytical model - Branković, Srbobran (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2014)
This paper presents the Symbols Research software (SR) – logical model and research tool that provides new opportunities in the field of empirical research of communication. SR collects and reviews the entire communication on social networks in a given time and social space and automatically detects the required content. In real time it sorts the material, creates basic overview, notices certain regularities and presents analytical findings. The model itself is a kind of artificial intelligence because it imitates the human brain: the operators who monitor the effectiveness of the so-called table of symbols (instrument for the content identification, classification and evaluation), continuously control its sensitivity and efficiency during the research process, enter corrections, and then these corrections are applied as a rule for future processing of material, which makes the instrument constantly improved. Almost in parallel, or with the postponement of a few seconds, the second and third level of processing are performed: simple analytics and results presentation, and then more complex analyses –multivariate and regression analysis as well as statistical procedure similar to the structural equation modeling. The SR concept and software can never be regarded as final and complete, or more precisely, they are and they must be flexible as well as the subject of continuous upgrading and improvements. Key words: content analysis, communication, social networks, methodology, advanced research, artificial intelligence